Analisis in silico pasangan miRNA-mRNA pada sindrom metabolik dan Parkinson: Hubungan molekuler dan potensi biomarker - Milas Siswanto, Ferbian; Handayani, Maria Dara Novi; Dewi, Rita; Novelya , Novelya; Wijaya, Ferdian Manuel; Finnegan, Meisy (Atma Jaya Catholic University of Indonesia, 2024)
Introduction: Parkinson's disease (PD) is the second most common neurodegenerative disease. Identification of PD biomarkers is critical for early diagnosis and development of therapeutic targets. There are many factors that are associated with PD, including metabolic syndrome (MetS). However, molecular links between MetS and PD for biomarkers is still a challenge. This study aims to determine the molecular links between MetS and PD using an in silico approach. Methods: Data were obtained from Gene Expression Omnibus to identify differentially expressed genes (DEGs) and microRNA (DEMs) in PD and MetS. DEGs were mapped to protein-protein interaction (PPI) networks using the STRING platform. Then, gene ontology (GO) and pathway analysis was performed with EnrichR to reveal specific and overlapped biological processes. Finally, microRNA (miRNA) and mRNA pairs were predicted using TargetScan. Results: A total of 25 DEGs were identified in both MetS and PD. GO and pathway analysis for MetS-PD revealed that these DEGs mainly related to metabolic and cytokine pathways. Examination of miRNA showed that hsa-miR-631 was down-regulated in both MetS and PD. GO and pathway analysis on predicted targets of hsa-miR-631 showed major changes in metabolic pathways. Hsa-miR-631 can target the 3' UTR of ATP2B4 at poorly conserved site, indicating a specific miRNA-mRNA pairing in humans. Conclusion: In patients with MetS and PD, hsa-miR-631 and ATP2B4 are depleted and elevated, respectively. Bioinformatic analysis indicates that ATP2B4 is a target of hsa-miR-631. We demonstrate for the first time that hsa-miR-631/ ATP2B4 pair is potential biomarker for PD due to MetS.